Robust intrapulmonary CD8 T cell responses and protection with an attenuated N1L deleted vaccinia virus. - Anuja Mathew; Joel O'Bryan; William Marshall; Girish J Kotwal; Masanori Terajima; Sharone Green; Alan L Rothman; Francis A Ennis (PLoS ONE)
Background Vaccinia viruses have been used as a model for viral disease and as a protective live vaccine. Methodology and principal findings We investigated the immunogenicity of an attenuated strain of vaccinia virus engineered to inactivate the N1L gene (vGK5). Using the intranasal route, this recombinant virus was 2 logs less virulent compared to the wildtype VACV-WR. Infection by the intranasal, intraperitoneal, and tail scarification routes resulted in the robust induction of cytolytic virus-specific CD8 T cells in the spleens and the lungs. VACV-specific antibodies were also detected in the sera of mice infected 3-5 months prior with the attenuated vGK5 virus. Finally, mice immunized with vGK5 were significantly protected when challenged with a lethal dose of VACV-WR. Conclusions These results indicate that the attenuated vGK5 virus protects against subsequent infection and suggest that the N1L protein limits the strength of the early antiviral CD8 T cell response following respiratory infection.